Differences in Complete Blood Results and Nutritional Status of Patients with Cleft Lip and Palate at the CLP Center in University of Muhammadiyah Malang from 2020 to 2022 - Feby Alfina Damayanti; Ruby Riana Asparini; Kusuma Andriana; Diah Hermayanti (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2025)
Background: Patients with Cleft Lip (CL) and Cleft Lip and Palate (CLP) have difficulties with eating and breastfeeding, which makes them more susceptible to malnutrition (measured using the z-score parameter) and infections. CLP is caused by inappropriate levator palatini muscles and velopharyngeal insufficiency, which can lead to infection, inflammation, and allergies that can affect the immune system. The immune system responds to these components with leukocytes, particularly neutrophils, eosinophils, and lymphocytes. Objective: To determine the difference in complete blood results and nutritional status between cleft lip and cleft palate at the CLP Centre Faculty of Medicine, University of Muhammadiyah Malang in 2020-2022.    Methods: The research was conducted at the CLP Centre FK UMM using observational methods with a total sample size.      Results: The study found that males had a higher prevalence of CL and CLP. The most common z-score for patients with CL and CLP was below average for those under 24 months old, and above average for those over 35 months old. Extremely low z-scores were more common in CLP patients aged between 24 and 35 months. Patients with CL and CLP were less likely to have anemia, and there was no correlation between the z-score and anemia. Patients below 2 years old with CL and CLP had normal white blood cell counts, while those over 2 years old had higher levels of white blood cells, mainly neutrophils and lymphocytes. Eosinophilia, a condition with high levels of eosinophils, occurred only in patients with CL. Only lymphocytes showed statistically significant hematological values, with a p-value of 0.021 (p<0.05).             Conclusion: It has been found that patients with CL and CLP have a statistically significant difference in their lymphocyte cells. Most cases of nutritional status issues occur in children younger than 24 months with a normal z-score. In contrast, children aged 24-35 months with an inadequate z-score are more likely to have nutritional issues in cases of CLP.